The effect of Artichoke (Cynara scolymus L.) on the expression of calcium-binding proteins in the eggshell gland of laying hens - Abadjieva, D.; Ankova, D.; Grigorova, S.; Kistanova, E. (Polish Journal of Veterinary Sciences, 2021)
The purpose of the present work is to investigate the effect of dietary-supplemented artichoke ( Cynara scolymus L.) on the mRNA expression of calbindin 1 ( Calb1), osteopontin ( Spp1), albumin ( Alb) and CALB1 protein in the eggshell gland (ESG) of laying hens. A total of 80 ISA Brown hens (each at 40 weeks of age) were randomly divided into two groups: a control and a treated group. All poultry received 130 g/day of compound feed for laying hens but the treated hens’ diet was also supplemented with 3g/kg of dried and milled artichoke ( Cynara scolymus L.). The increase of the Ca content in blood of the treated hens was established. Significantly decrease of Spp1 mRNA transcripts was found in the eggshell gland of the treated hens, while the mRNA level of Alb was increased. The relative expression of Calb1 mRNA tended to increase in the treated group. The expression of calbindin protein in the cytoplasm of glandular cells of the shell gland was defined by immunohistochemical method. Very strong signals of calbindin were observed in the treated group. The supplementation of the laying hens’ diet with dried artichoke ( C. scolymus L.) led to a significant increase of Ca content in blood that was reflected in the changes of expression of the eggshell gland genes involved in the mineralization of eggshell.
Keywords: hens; egg shell gland; genes; artichoke